2019
DOI: 10.1021/acsami.8b22748
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Thermosensitive Liposomes Based on Natural Phase-Change Material: Near-Infrared Light-Triggered Drug Release and Multimodal Imaging-Guided Cancer Combination Therapy

Abstract: Multifunctional theranostic nanoplatforms (NPs) in response to environment stimulations for ondemand drug release are highly desirable. Herein, the nearinfrared (NIR)-absorbing dye, indocyanine green (ICG), and the antitumor drug, doxorubicin (DOX), were efficiently coencapsulated into the thermosensitive liposomes based on natural phase-change material. Folate and conjugated gadolinium (Gd) chelate-modified liposome shells enhance active targeting and magnetic resonance performance of the NPs while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 56 publications
(98 reference statements)
1
100
0
Order By: Relevance
“…[4][5][6][7] Except for the use as a drug delivery carrier, theranostic liposomes have been concerned more and more in recent years due to the demand of the simultaneous diagnosis and therapy. Such theranostic liposomes are commonly obtained by the co-encapsulation of drugs and imaging molecules, such as uorescent quantum dots, 8,9 magnetic resonance imaging contrast agents (MRI CAs), [10][11][12][13] CT imaging contrast agents, 14 photoacoustic imaging CAs, 15 and ultrasound imaging CAs. 16 Among them, MRI-based theranostic liposomes own special advantages, because MRI is a widely used non-invasive medical imaging technique in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Except for the use as a drug delivery carrier, theranostic liposomes have been concerned more and more in recent years due to the demand of the simultaneous diagnosis and therapy. Such theranostic liposomes are commonly obtained by the co-encapsulation of drugs and imaging molecules, such as uorescent quantum dots, 8,9 magnetic resonance imaging contrast agents (MRI CAs), [10][11][12][13] CT imaging contrast agents, 14 photoacoustic imaging CAs, 15 and ultrasound imaging CAs. 16 Among them, MRI-based theranostic liposomes own special advantages, because MRI is a widely used non-invasive medical imaging technique in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects have been discussed in published studies: classification of PCMs, encapsulation shell materials, microencapsulation techniques, PCM microcapsules' characterizations, and thermal applications. [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] This review aims to help the researchers from various fields better understand the PCM microcapsules and provides critical guidance for utilizing this technology for future thermal energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…As both COi6‐4Cl NPs and ICG can be irradiated by 808 nm laser, the ROS quantum yield (Φ ∆ ) of COi6‐4Cl NPs can be calculated by the comparison with ICG (Φ ∆ of 0.2% according to the previous report). [ 17 ] The result revealed that COi6‐4Cl NPs showed a Φ ∆ of 2.7%, which was 13‐fold higher than that of ICG (Figure S10, Supporting Information). Moreover, 20 and 60 wt% loading COi6‐4Cl NPs showed very similar Φ ∆ values (2.7% vs 2.3%) when the molar concentrations of COi6‐4Cl were kept constant, which indicated that the photosensitizing properties of COi6‐4Cl were barely affected by the aggregation state.…”
Section: Methodsmentioning
confidence: 99%